The relationship of continuous improvement and cleaner production on operational performance: An empirical study in electronic manufacturing firms, Taiwan China - Tseng, Ming Lang (Animo Repository, 2006)
Recent research has pointed out the limitations of achieving commitment and continuous improvement in cleaner production program implementation. And cleaner production designed to reduce wastes and emissions at source can improve the environmental, as well as economic performance of participating organization. However, there is inadequant empirical evidence or model to prove the relationship of cleaner production, continuous improvement and operational performance existed. This paper investigates the effects of continuous improvement and cleaner production on operational performance. A conceptual model is developed and three research hypotheses are empirically examined using structural equation modeling. The data were collected via a survey of Taiwan electronic manufacturing firms. The result indicated that cleaner production has a positive influence on operational performance as well as on the continuous improvement on cleaner production and operational performance. Theoretical, managerial and research implications are discussed. © 2006 Taylor & Francis Group, LLC.